Clinical cure induced by pegylated interferon α-2b in the advantaged population of chronic hepatitis B virus infection: a retrospective cohort study - Wen, Chaojing; Wang, Yixuan; Tian, Haoyue; Lei, Yu; Wang, Zhiyi; Cai, Dachuan; Zhou, Zhi; Shi, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2024)
Background Among the advantaged population with clinical cure of chronic hepatitis B, chronic inactive hepatitis B virus carriers (IHCs) and nucleoside analog-experienced patients have similar serological manifestations. This study established non-interferon-treated groups as controls to compare the efficacy of pegylated interferon α-2b (Peg-IFNα-2b) in achieving clinical cure between IHCs and nucleoside analog (NA)-experienced patients. Method A total of 270 patients were enrolled in this observational study. The IHC cohort comprised 55 patients who received Peg-IFNα-2b (Peg-IFN group), and the other 70 patients did not receive any antiviral treatment (untreated group). Patients treated with NAs were divided into two groups: one group (70 patients) receiving NA add-on Peg-IFNα-2b therapy regimen (NA add-on Peg-IFN group) and another group (75 patients) receiving continuous NA monotherapy (NA group). The primary endpoints were hepatitis B surface antigen (HBsAg) clearance and HBsAg seroconversion at 48 weeks and 72 weeks. Results At 48 weeks, 65.5% (36/55) and 52.9% (37/70) patients achieved HBsAg clearance in the Peg-IFN group and NA add-on Peg-IFN group, respectively (p = 0.156). HBsAg seroconversion was achieved in 47.3% (26/55) of the Peg-IFN group and 34.3% (24/70) of the NA add-on Peg-IFN group (p = 0.141). At the follow-up of 72 weeks, 36 patients in the Peg-IFN group achieved HBsAg loss (65.5%, 36/55), and 33 patients in the NA add-on Peg-IFN group achieved HBsAg clearance (47.1%, 33/70), which were significantly higher than in the Peg-IFN group (p = 0.041). The HBsAg seroconversion rates in the Peg-IFN group and NA add-on Peg-IFN group at 72 weeks were 45.5% (25/55) and 32.9% (23/70), respectively (p = 0.151). No patient achieved HBsAg clearance or seroconversion in the NA group and untreated group. Furthermore, the receiver operating characteristic curve showed baseline HBsAg< 72 IU/mL, and the decline of HBsAg of more than 80% and 98% from baseline to 12 and 24 weeks provided good predictions for HBsAg clearance. Meanwhile, 77% of patients with baseline HBsAg< 100 IU/mL achieved a clinical cure at 48 weeks. Conclusion Peg-IFNα-2b results in a high rate of HBsAg clearance and seroconversion in both IHCs and NA-experienced patients, especially for those patients who have HBsAg below 100 IU/mL.